Naḥwa al-Tafattuḥi al-Islāmī: I’ādat binā’ al-Fikr al-Islāmī bi Indūnīsīyā - Tasman, Tasman (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2010)
This article discusses about Islamic thinking on religious diversity in Indonesia. Indonesia is one of the most pluralist countries in the world because of its diverse ethnic groups and religions. Although the majority of its population are Muslim, the country has become neither a religious nor a secular state. In this country, every citizen regardless of his or her religious background has the freedom to express their belief and faith as long as they abide to the religious tolerance established by the state (kerukunan hidup beragama), and does not impinge on other religious institutions.DOI: 10.15408/sdi.v17i2.464